The experiences of older individuals providing care to older dependents: A phenomenological study in Spain - Alcañiz Garrán, María del Mar; Garcia-Sanjuan, Sofia; Ramos-Pichardo, Juan Diego; Sanjuan-Quiles, Angela; Montejano Lozoya, Raimunda (Public Library of Science (PLoS), 2021)
Objective: Non-professional care provided in domestic settings by a family member or someone from the close environment and without a connection to a professional care service, is increasingly assumed by older people, mainly the spouses of those requiring care. The aim of this study was to describe the experience of older people providing care at home to older dependents. Methods: A qualitative study was carried out to describe and explore the experience of older people, caregivers of dependent older people in the home. Results: Four themes emerged as a result of the analysis: interpersonal relationships established in the caregivers’ immediate environment; the need and request for public and private resources; consequences of providing care during old age; and adaptation to the circumstance of being a caregiver during old age. Older people who provide home-based care, experience their situation as stressful, feel that it limits their daily life, deprives them of their freedom, and affects their interpersonal relationships and social activities. Discussion: Older caregivers learn quickly and can manage the skills issues. The volume of work is their challenge. Interpersonal relationships are altered depending on the length of time spent together and the demand for care. Public services and benefits are not adapted to the demands of caregivers or dependent persons.
Keywords: Older people; Older dependents; Non-professional care; Qualitative study